Teaching conflicts of interest and shared decision-making to improve risk communication: a randomized controlled trial - Koch, Cora; Dreimüller, Nadine; Weißkircher, Janosch; Deis, Nicole; Gaitzsch, Eva; Wagner, Stefanie; Stoll, Marlene; Baessler, Franziska; Lieb, Klaus; Jünger, Jana (Journal of general internal medicine, 2020)
Risk communication is a core aspect of a physician’s work and a fundamental prerequisite for successful shared decision-making. However, many physicians are not able to adequately communicate risks to patients due to a lack of understanding of statistics as well as inadequate management of conflicts of interest (COI).
Published online December 10, 2019
Gesehen am 08.04.2020